Pharmacokinetics and pharmacodynamics of ch14.18/CHO in relapsed/refractory high-risk neuroblastoma patients treated by long-term infusion in combination with IL-2. Issue 3 (2nd April 2016) - Siebert, Nikolai; Eger, Christin; Seidel, Diana; Jüttner, Madlen; Zumpe, Maxi; Wegner, Danilo; Kietz, Silke; Ehlert, Karoline; Veal, Gareth J.; Siegmund, Werner; Weiss, Michael; Loibner, Hans; et al.
ABSTRACT: Ch14.18 manufactured in Chinese hamster ovary (CHO) cells is currently being evaluated in clinical trials. Short-term infusion (STI) (8–20 h/day; 4–5 days) of 100 mg/m2 ch14.18/CHO (dinutiximab β) per cycle in combination with cytokines is standard treatment of neuroblastoma (NB) patients. As pain is a limiting factor, we investigated a novel delivery method by continuous long-term infusion (LTI) of 100 mg/m2 over 10 days. 53 NB patients were treated with 5–6 cycles of 6 × 106 IU/m2 subcutaneous interleukin-2 (d 1-5, 8-12), LTI of 100 mg/m2 ch14.18/CHO (d 8-18) and 160 mg/m2 oral 13-cis-retinoic acid (d 22-35). Human anti-chimeric antibody (HACA), antibody-dependent cell-mediated cytotoxicity and complement-dependent cytotoxicity were determined. With LTI, we observed a maximum concentration of ch14.18/CHO (Cmax) of 12.56 ± 0.68 µg/ml and a terminal half-life time (t1/2 β) of 32.7 ± 16.2 d. The clearance values for LTI and STI of 0.54 ± 0.13 and 0.41 ± 0.29 L/d m2 and area under the serum concentration-time curve (AUC) values of 189.6 ± 41.4 and 284.8 ± 156.8 µg×d/ml, respectively, were not significantly different. Importantly, we detected ch14.18/CHO trough concentration of ≥ 1 µg/ml at time points preceding subsequent antibody infusions after cycle 1, allowing a persistent activation of antibody effector mechanisms over the entire treatment period of 6 months. HACA responses were observed in 10/53 (19%) patients, similar to STI (21%), indicating LTI had no effect on the immunogenicity of ch14.18/CHO. In conclusion, LTI of ch14.18/CHO induced effector mechanisms over the entire treatment period, and may therefore emerge as the preferred delivery method of anti-GD2 immunotherapy to NB patients.